2017
DOI: 10.1159/000478990
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Outcomes and Early Survival in Octogenarians Who Underwent Radical Cystectomy for Bladder Cancer

Abstract: Objective: To evaluate perioperative outcomes and early survival in a series of octogenarians who underwent radical cystectomy (RC) and urinary diversion for bladder cancer. Patients and Methods: We retrospectively evaluated the clinical records of 44 patients aged ≥80 years who underwent open RC and urinary diversion at 2 high-volume centers between July 2013 and December 2015. Estimated blood loss (EBL), transfusion rate, and length of hospital stay (LOS) were evaluated. Ninety-day postoperative complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…Since almost every patient received incontinent UD in the United States, the clinical selection of older and frailer patients is likely to be masked [17]. Although these results imply a careful selection of older patients for RC, current studies showed acceptable rates of complications and mortality when older patients were treated in surgical centers [9].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Since almost every patient received incontinent UD in the United States, the clinical selection of older and frailer patients is likely to be masked [17]. Although these results imply a careful selection of older patients for RC, current studies showed acceptable rates of complications and mortality when older patients were treated in surgical centers [9].…”
Section: Discussionmentioning
confidence: 82%
“…The morbidity and mortality are among the highest in oncological surgery [3][4][5][6][7]. Influential factors are the high level of invasiveness combined with patient-derived factors such as the elevated mean patient's age and greater comorbidity [4,6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite data stated before, classic practice is to preserve QoL of elderly patients with an IC derivation [9], and to take advantage of its acceptable rate of major complications and mortality in octogenarians [10]. …”
Section: Discussionmentioning
confidence: 99%
“…Obviously, the high percentage of missing data (69%) is a strong limitation of the BAUS study preventing any consideration about this important outcome. In our experience, the 3-mo mortality rate ranged between 2% and 3% of cases, with higher percentage in patients aged >80 years ( 13 , 16 , 22 ). These percentages seem to be similar to those reported in contemporary RARC series ranging from 1% to 3.5% 3-mo after RARC ( 18 ).…”
mentioning
confidence: 69%